'I have neither his voice nor body': upper secondary schoolteacher students experiencing gendered division of labor. Issue 5 (4th July 2021) - Persson, Magnus
ABSTRACT: For this study, Swedish upper secondary schoolteacher students were interviewed about their experiences and perceptions of teacher work in light of the traditional gendered division of labor in teaching. While female teaching has been signified by caring work, male teaching has been signified by distant teacher-pupil relations and the use of bodily resources to discipline pupils. In this study, both genders expressed feeling comforted when teacher practice corresponded to the traditional gendered division of labor and experiencing unease when it did not. Women expressed shortcomings in their ability to perform authoritative work because of their lack of male bodily resources. This subordination has been understood as symbolic violence, processed by a gendered habitus that structures women to prefer a special type of teacher work. Despite a small female majority in the profession and in teacher education, male domination still permeates the professional properties of the upper secondary schoolteacher work.